Is TikTok a new job board? / Mohd Fazil Jamaludin ... [et al.] - Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz; Adzahar, Khairul Azfar (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Resume is one of the important documents for a job hunter. Traditionally, writing a resume and has it ready at hand is the only accepted method. Fast forward, everything is now done electronically. According to Frankel (2016), while the resume may never be printed in this digital age, applicants should be aware that they can send the document in an easily-readable format that is compatible with all screen sizes, for instance, in PDF format. Job seekers may utilise job boards to find job opportunities in their geographic region and profession. Jobstreet, as well as MyFutureJobs and other prominent platforms (LinkedIn) are very widely recognised job boards in Malaysia. Some Gen Z-ers feel limited by LinkedIn and they are now using TikTok resumes for job applications (Lorenz, 2021). Employers have recently realised that this is a trend.